Effects of a 1-mm difference in bearing thickness on intraoperative bearing movement and kinematics in Oxford unicompartmental knee arthroplasty - Kohei Kawaguchi; Hiroshi Inui; Shuji Taketomi; Ryota Yamagami; Kenichi Kono; Shin Sameshima; Tomofumi Kage; Sakae Tanaka (BMC Musculoskeletal Disorders, 2022)
Abstract Background The choice of mobile bearing (MB) thickness is essential for obtaining successful results after mobile-bearing Oxford unicompartmental knee arthroplasty (UKA). This study aimed to investigate the effects of a 1-mm difference in bearing thickness on intraoperative MB movement and intraoperative knee kinematics in Oxford UKAs. Methods We prospectively investigated the effects of a 1-mm difference in bearing thickness on intraoperative MB movement and knee kinematics in 25 patients who underwent Oxford UKAs when surgeons didn’t know which bearing thickness to choose with 1-mm difference. A trial tibial component that was scaled every 2 mm was used to measure the intraoperative MB movement, and the tibial internal rotation relative to the femur and the knee varus angle was simultaneously evaluated using the navigation system as the knee kinematics. We separately evaluated sets of two MB thicknesses with 1-mm differences, and we compared the intraoperative parameters at maximum extension; 30º, 45º, 60º, and 90º flexion; and maximum flexion between the thicker MB (thick group) and the thinner MB (thin group). Results The MB in the thin group was located significantly posteriorly at 90º flexion compared with that in the thick group; however, there were no differences at the other flexion angles. There was significantly less tibial internal rotation in the thin group at 90º flexion than that in the thick group; however, there were no differences at the other flexion angles. The knee varus angles in the thick group were significantly smaller than those in the thin group by approximately one degree at all angles other than at 30º and 45º flexion. Conclusion The thicker MB could bring the less posterior MB movement and the more tibial internal rotation at 90º flexion, additionally the valgus correction angle in the thicker MB should be paid attention. These results could help surgeons to decide the thickness of MBs when they wonder the thickness of MB.